Impact of range bar and ergodic process on early price trend detection using evidences from USD/CNY currency - Pang, Tor Nee (2021)
This research uses ergodic theory to study early price trends for USD/CNY currency in China. The motivation of this study is to detect early price trends within two standard deviations away from average prices. Researchers can find the current method in forecasting the price trend after two standard deviations from the average prices named “trend following” methodology, which has caused two gaps experienced by prior researchers. Without this research, the first gap is failure price trend formation within two standard deviations away from average prices that cause researchers cannot collect sufficient valuable samples to justify their hedge position. The second gap is lagging higher prices after two standard deviations from the average prices during trend following that causes researchers to select price to overvalue sample. This research introduces a solution for preventing failure price trend formation within two standard deviations and lagging higher price after two standard deviations prevention. Hence, this research is motivated to introduce range bar as a mediator variable and ergodic theory to support ergodic process as a moderator variable to create a new model. First, the range bar serves as a mediator to replace minutes of each bar time interval to make a recent sample of a non-periodic bar during the range-bound trading period. The objective is to select a successful price trend formation sample within two standard deviations away from moving average prices to hypothesize effectiveness by achieving at least 68% of frequency mean. Second, the ergodic process serves as a moderator to analyze a new sample of a non-periodic bar during the rangebound trading period within two standard deviations away from average prices. The objective is to choose a price to undervalue sample to hypothesize effectiveness by achieving at least a 0.8 correlation coefficient. This research tends to enhance the accuracy of price trend analysis during early detection within two standard deviations. It is possible to save up to 1.3% (statistic estimation) or USD54 billion of USD4.15 trillion annual foreign exchange between 2015 to 2019 by applying range bar and ergodic process variables. The future direction would replicate Malaysia to improve market liquidity.